2019
DOI: 10.1016/j.ympev.2019.106581
|View full text |Cite
|
Sign up to set email alerts
|

Diversification history in the Dendrocincla fuliginosa complex (Aves: Dendrocolaptidae): Insights from broad geographic sampling

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 79 publications
2
16
0
3
Order By: Relevance
“…Importantly, a recent phylogeographic study (Schultz et al. ) sequenced a single nuclear gene and mitochondrial DNA for all subspecies of D. fuliginosa and found that the four subspecies that we failed to sample do not represent genetically diverged lineages but rather were nested phylogenetically within subspecies we did sample (e.g., D. f. lafresnayei is nested within the sampled D. f. ridgwayi ; D. f. deltana , and D. f. barinensis were nested with the sampled D. f. meruloides ; D. f. phaeochroa was nested with the sampled D. f. neglecta ). We thus had complete sampling of all phylogenetically distinct subspecies within D. fuliginosa .…”
Section: Methodsmentioning
confidence: 75%
See 4 more Smart Citations
“…Importantly, a recent phylogeographic study (Schultz et al. ) sequenced a single nuclear gene and mitochondrial DNA for all subspecies of D. fuliginosa and found that the four subspecies that we failed to sample do not represent genetically diverged lineages but rather were nested phylogenetically within subspecies we did sample (e.g., D. f. lafresnayei is nested within the sampled D. f. ridgwayi ; D. f. deltana , and D. f. barinensis were nested with the sampled D. f. meruloides ; D. f. phaeochroa was nested with the sampled D. f. neglecta ). We thus had complete sampling of all phylogenetically distinct subspecies within D. fuliginosa .…”
Section: Methodsmentioning
confidence: 75%
“…Most subspecies were monophyletic with strong support with three exceptions: support for monophyly of D. m. merula and D. m. obidensis was low, D. m. castanoptera was paraphyletic with respect to D. m. badia (with our sole sample of D. m. castanoptera from the interfluve between the Xingu and Tocantins rivers grouping with D. m. badia , suggesting that populations from this interfluve should either be transferred to D. m. badia or be recognized as a new subspecies) and the two samples of D. f. meruloides were nested within those of D. f. neglecta , contrary to two studies that found these taxa to be reciprocally monophyletic, but whose analyses were based on few genes and were dominated by a mitochondrial DNA signal (Weir and Price ; Schultz et al. ).…”
Section: Resultsmentioning
confidence: 87%
See 3 more Smart Citations